Relationship between sleep patterns and hypertension incidence among young adults at Medan Johor Primary Health Center - Yolanda Yestifany Br. Sembiring; Putri Yunita Pane; Rapael Ginting; Deza Yumardika; Felanda Ahsanu Nadia; Rudi Chandra; Widyaningsih Oentari (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Hypertension is a non-communicable disease that remains a public health problem with increasing prevalence. One factor hypothesized to be associated with hypertension is sleep pattern. Poor sleep pattern may affect the cardiovascular system through increased sympathetic nervous system activity, contributing to elevated blood pressure. This study aimed to analyze the relationship between sleep pattern and the incidence of hypertension among young adults (aged 20–40 years) in the working area of Medan Johor Community Health Center.  Method: This quantitative study used a cross-sectional design. A sample of 100 respondents was selected using stratified random sampling. Sleep pattern data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and hypertension status was determined through direct blood pressure measurement. Univariate and bivariate analyses were performed using the Chi-square test with a 95% confidence level. Results: Most respondents had poor sleep patterns (69.0%) and were hypertensive (68.0%). All respondents with good sleep patterns had normal blood pressure (31 respondents, 100.0%), whereas among those with poor sleep patterns, 68 (98.6%) were hypertensive. The Chi-square test yielded p < 0.001, indicating a significant relationship between sleep pattern and hypertension among young adults in this population. Conclusion: There is a significant relationship between sleep pattern and hypertension incidence in young adults. Improving sleep quality and duration should be promoted as part of hypertension prevention efforts.